Assertive use of transmedia storytelling and Information and Communication Technology as tools to foster learning - Cunha, Arielly Kizzy [UNESP]; Bizelli, Jose Luis [UNESP]; Santos Cruz, Jose Anderson [UNESP]; Leite da Silva, Alexander Vinicius (Editora Univ Leopoldlanum, 2021)
Technological innovations and contemporary social concepts - virtual, digital, ephemeral, competitive, imagery - favor the development of new educational processes and the inclusion of these technologies as tools to foster learning. Educators, parents, children and professionals producing these contents are involved in the process. The study aims to reflect on the characteristics of digital natives, children, players, viewers, consumers, and content producers, requiring a multidisciplinary team of story, audiovisual and game producers. Through literature review and content analysis and synthesis, changes in actions related to the development and importance of Transmedia Storytelling are observed and verified for individuals of this generation, and these products are already part of their lives, and their use can be beneficial if mediated, directed and planned by those in charge, educators and the team of professionals who produce them.
Keywords: Transmedia Storytelling; Technology; Information; Communication; Education